Organic Nitrogen Forms in Soils Treated with Cattle Manure - Adame, Cassia Rita [UNESP]; Carlos, Roberta Souto [UNESP]; Braos, Lucas Boscov; Ferreira, Manoel Evaristo [UNESP]; da Cruz, Mara Cristina Pessôa [UNESP] (MDPI, 2024)
The availability of nitrogen in the soil is influenced by several factors associated with the forms and characteristics of organic nitrogen present in it, as well as by any property that impacts its microbiological and biochemical activity. The objective of the present work was to evaluate the combined effect of manure fertilization, soil type, and incubation time on soil N forms and availability. The experiment was conducted in a factorial scheme (2 soils × with (20 Mg ha−1) or without manure × 4 incubation times (15, 45, 90, and 180 days)). The levels of organic matter and fractions of organic N and mineral N were evaluated. Fertilization increased the organic matter and mineral N content in both soils, but the effect of fertilization on the organic N fractions was different depending on the type of soil. In the clayey soil, there was an accumulation of nitrogen in the unidentified hydrolysable fraction, whereas, in the sandy soil, the greatest increase occurred in the hydrolysable ammonium fraction. The application of manure generated different effects on the dynamics of N forms, depending on the type of soil. It is important to understand the impacts of different soil properties on the forms of nitrogen.
Keywords: direct steam distillation method; N availability; N organic fractionation; organic fertilization; potentially available N